Lean change - Anderson, Jeff (Addison-Wesley, 2014)
"In Lean Change LiveLessons, Jeff Anderson and Alexis Hui provide training on how to manage Lean and Agile change initiatives using the Lean Change method. Change agent will learn how to leverage two key concepts, negotiated change and validated learning, to iterate through an Agile change. By the end of the LiveLessons, viewers will be equipped with a set of tools to start applying to their Agile change initiatives. The lessons cover the need for the Lean Change method, how to use the Lean Change Canvas to develop and manage a change plan, how to build learning into the change process through the use of the Validated Change lifecycle, and how to scale Lean Change tools to manage Agile transformations at scale."--Resource description page.
Title from title screen
Keywords: Organizational effectiveness; Lean manufacturing; Agile software development; Efficacité organisationnelle; Production allégée; Méthodes agiles (Développement de logiciels)